Hypercholesterolemia alters vascular functions and gene expression of potassium channels in rat aortic smooth muscle cells - Ren Ya-Jun; Xu Xiang-Hua; Zhong Chong-Bo; Feng Nan; Wang Xiao-Liang (Acta Pharmacologica Sinica; Vol 22, No 3 (March 2001): Acta Pharmacologica Sinica, 2016)
Aim: To investigate the effects of hypercholesterolemia on functions of rat aorta and on gene expression of inward rectifier and ATP-sensitive potassium channels in aortic smooth muscle. Methods: Rats were treated with high-cholesterol emulsion ig for 2 weeks; the aortic rings with and without endothelium were prepared to examine the aortic contractile and relaxation responses; RT-PCR was used to observe the gene expression of inward rectifier and ATP-sensitive potassium channels. Results: Hypercholesterolemia damaged the endothelium-dependent vascular functions severely, but did not affect the endothelium-independent vascular functions; Kir6.2 mRNA expression was upregulated (P < 0.05) and Kir3.1 mRNA expression was downregulated markedly (P < 0.05) in hypercholesterolemic smooth muscle. Conclusion: Hypercholesterolemia altered the vascular functions and regulated gene expression levels of specific inward rectifier and ATP-sensitive potassium channel subtypes.